Bentuk Penyajian Kesenian Singa Depok Di Desa Lingga Kuamang Dalam Acara Khitanan - Desi Kumalasari; Marzam Marzam (FBS Universitas Negeri Padang, 2020)
This research aims to reveal the form of the art presentation of Singa Depok in circumcision event in the village of Lingga Kuamang. This research is a qualitative research using descriptive methods. The main instrument in this research was the researcher itself and was assisted by supporting instruments such as stationery and cameras. The data were collected through library study, observation, interview, and documentation. The data analysis was conducted by collecting the data, classifying the data, describing the data, and making conclusion. The results show that Singa Depok art is still performed as an entertainment in the circumcision event in the village of Lingga Kuamang, and Singa Depok show is not obliged to West Java or Sundanese people. As the time changes, Singa Depok has undergone changes in term of the songs played, lion Dolls used as the instrument, and players. Although the inhabitants in the village of Lingga Kuamang are diverse in tribes, it does not make this art disappear. It is due to the fact that the change of the song performed can still be enjoyed by the people watching it. In addition, Singa Depok art has its own characteristic. Thus, Singa Depok art is as an entertainment for the mind of circumcised children.